Interest in Visiting in Terms of City Branding and City Image in Bantimurung Tourism Objects Mars County - M. Yusuf Alfian Rendra Anggoro KR; Muhammad Yusuf; Lina Mariana; Nur Sandi Marsuni (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This study aims to find out 1) the description of visiting interest, city image and city branding at the Bantimurung tourist attraction, Maros Regency, 2) the influence of city branding and city image together on visiting interest in Bantimurung attractions, Maros Regency, 3) the influence of city branding on the interest in visiting the Bantimurung tourist attraction, Maros Regency, 4) the influence of city image on the interest in visiting the Bantimurung tourist attraction, Maros Regency. The population in this study were all visitors to the Bantimurung tourist attraction who obtained a sample using a purposive random sampling technique, which was carried out first Calculation of the minimum number of samples using the Cochran formula in order to obtain a total sample of 96 people. The data collection technique used was a Likeart scale questionnaire in which the development of instruments for each variable was tested for content validity using the Gregory formula, construct validity testing using Comfirmatory Factor Analysis (CFA) and instrument reliability testing using the Alpha Conbach formula. The data analysis technique used is descriptive statistics and multiple and partial regression statistics. The results of the study reveal that 1) the description of interest in visiting Bantimurung tourism objects is generally categorized as high, the description of city branding is generally categorized as low and the description of city image is generally categorized as good. 2) there is the influence of city branding and city image together on the interest in visiting the Bantimurung tourist attraction, Maros Regency, the magnitude of the influence together is 66%. 3) there is a positive and significant influence of city branding on the interest in visiting the Bantimurung tourist attraction, Maros Regency, and 4) there is a positive and significant influence of city branding on the interest in visiting the Bantimurung tourist attraction, Maros Regency.